2012
DOI: 10.1039/c1cp22390a
|View full text |Cite
|
Sign up to set email alerts
|

The ethanol electrooxidation at Pt layers deposited on polycrystalline Au

Abstract: The ethanol electro-oxidation reaction was evaluated using a polycrystalline Au substrate modified with two different amounts of Pt using the galvanic exchange methodology. FTIR results suggest that Pt deposits have a greater ability to break the C-C bond present in the ethanol molecule. However, under potentiostatic conditions both modified Au surfaces undergo faster deactivation in comparison with polycrystalline platinum as indicated by the chronoamperometric results. XPS results indicate the presence of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The Pt peak position at −72.6 eV further suggests that the Pt monolayer exhibits Pt 2+ states . This finding is confirmed by the Pt 4d 5/2 level at −316.4 eV (inset in Figure a) . The weaker signal of Pt 4f in the XPS data indicates that the thickness of the Pt overlayer on Au-NI/Si is around 1 nm.…”
Section: Results and Discussionmentioning
confidence: 56%
“…The Pt peak position at −72.6 eV further suggests that the Pt monolayer exhibits Pt 2+ states . This finding is confirmed by the Pt 4d 5/2 level at −316.4 eV (inset in Figure a) . The weaker signal of Pt 4f in the XPS data indicates that the thickness of the Pt overlayer on Au-NI/Si is around 1 nm.…”
Section: Results and Discussionmentioning
confidence: 56%
“…For instance, Pt@Au core-shell nanoparticles and Pt layers on polycrystalline Au have been tested by several groups for catalytic reactions. [29][30][31][32][33] In this system, as well as in the case of the Pt/Au(hkl) model surfaces studied in this paper, redistribution of the catalytically active components may occur as a consequence of the adsorption of intermediate species (such as, but not limited to, CO), thus inducing variations (gain or loss) in the activity of the catalyst material depending on the reaction paths followed and the affinities between the reaction intermediates and each component of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the Faraday efficiency for the EOR C1 pathway on Pd-based and Pt-based catalysts is generally quite low (normally only 1–7.5% for Pt or ca. 2.5% for Pd) at room temperature, even if a ca. 24% Faraday efficiency was obtained on Pd–Ni­(OH) 2 /GO in alkaline media by Huang et al, and a much stronger capability for the C–C cleavage was observed on a non-alloyed Pt 46 –(SnO 2 ) 54 core–shell particle .…”
Section: Introductionmentioning
confidence: 99%